Trends of The Phytoplankton Community And Physical Chemical Factors As Determinants of Pollution Level In The Electric Steam Power Plant (ESPP) Teluk Sirih Waters - Gusna Merina; Indra Junaidi Zakaria; Ahmad Mursyid; Wandanil Putra; Rahma Wirni (Sriwijaya Journal of Environment, 2023)
The existence of the Electric Steam Power Plant (ESPP) in Teluk Sirih located on the seafront will certainly have an impact on changes in environmental factors such as physical, chemical and biological factors, because the water needed for the ESPP operational process comes from sea water. Changes in the physicochemical factors of sea surface water due to ESPP activity will affect organisms in these waters, one of which is phytoplankton. Therefore, the purpose of this research is to look at changes or trends in the phytoplankton community and its relation to pollution by the physics and chemistry of the waters around the ESPP Teluk Sirih. This research was conducted from June 2019 to June 2021, sampling was carried out annually for three years. This study used a purposive sampling method and plankton sampling using a plankton net horizontally, then the samples were taken to the laboratory for identification. Sampling of water physics and chemistry was carried out in situ and ex-situ, namely by being preserved for further transport to the laboratory. The results of this study indicate the trend of phytoplankton fluctuating from the number of abundance, taxa and diversity index. This is because the physicochemical factor also fluctuates, there is one parameter above the quality standard, namely phenol whose levels are more than 0.02 mg/l. However, it can be concluded that the condition of the waters in the ESPP Teluk Sirih is still in quite good condition.